2015
DOI: 10.1007/s11069-015-1845-0
|View full text |Cite
|
Sign up to set email alerts
|

Predicting small business demise after a natural disaster: an analysis of pre-existing conditions

Abstract: Few studies of small businesses have addressed demise in post-disaster environments, and the factors that lead to business demise after natural disasters are not well understood. This study explored demise by interviewing a random sample of small business owners whose businesses survived or met demise following Hurricane Katrina. The goal of this study was to determine whether businesses that met demise could be predicted based on pre-existing characteristics of those businesses and their owners. Findings indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 47 publications
7
128
0
1
Order By: Relevance
“…Previous literature showed that owner's gender makes a difference to the success of their business [13,14]. Female owners were less successful compared to male owners when facing natural disasters [15,16]. In another article, Danes et al [17] found that receiving assistance and resilience were statistically significant for both genders; it was positively associated with males and negatively associated with females.…”
Section: Owner Demographicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous literature showed that owner's gender makes a difference to the success of their business [13,14]. Female owners were less successful compared to male owners when facing natural disasters [15,16]. In another article, Danes et al [17] found that receiving assistance and resilience were statistically significant for both genders; it was positively associated with males and negatively associated with females.…”
Section: Owner Demographicsmentioning
confidence: 99%
“…Marshall et al [15] found that veteran-owned businesses had higher odds of closing after Hurricane Katrina. Marital status also affects business performance.…”
Section: Owner Demographicsmentioning
confidence: 99%
See 3 more Smart Citations